Social media addiction and its influence on mental health among university students in cambodia: beyond the cultivation theory - Math, Kreya; Wok, Saodah (Asian Scholar Network (002903215-H), 2020)
This study was set out to determine social media addiction and its influence on mental health among university students in Cambodia. The research paper identified the most used social media platform, level of social media addiction, and the relationship between social media addiction and mental health, in particular, depression, anxiety, and loss of concentration. It goes beyond the cultivation theory. The study employed a quantitative research design using a network sampling survey method with a self-administered questionnaire as the research instrument. Two hundred and twenty-four respondents participated in the survey. The findings indicate that Facebook is the most popular social media platform, followed by YouTube and Instagram. The level of social media addiction is not that serious with only slight addiction detected. There is a significant positive correlation between social media addiction and mental health, specifically loss of concentration, depression, and anxiety, in that sequence. Overall the study suggests that to avoid mental health issues (depression, anxiety, and loss of concentration), students should limit their time on social media and lower their dependency habit on them.